Speech act theory a historical development - Abdulhamzah, Ali (Technium Education and Humanities, 2025)
Speech act theory, from the perspective of pragmatics, is a concept that is continually developing within the realm of linguistics. While Austin and Searle’s models provided the conceptual frameworks that contribute to ongoing scholarship, contemporary research also identifies a need for further adapting established models as analysts examine issues impacting subjects, organizations, and nations in the 21st century. In this context, the primary objective of this article is to offer an overview of the historical evolution of Speech Act Theory and to illustrate how these theoretical evaluations enhance the dissertation's examination of speech acts as processes that impact distinct populations in diverse manners.